STUDI TENTANG PERUBAHAN TRADISI GONDANG BATAK TOBA PADA ERA MODERNISASI DI DESA TANAH MERAH KECAMATAN SIAK HULU - Teguh Pribadi; Hambali Hambali; Haryono Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstrack: This study aims to find out what aspects of change in Gondang Batak Toba tradision in the era of modernization in the village of Tanah Merah Subdistrict Siak Hulu and to know the factors that cause changers in the era of modernization Gondang tradition in the village of Tanah Merah Subdistrict Siak Hulu. As for who becomes the population in this research is the entire head of the Batak Toba language family are good christians or chatolikh. In the village of Tanah Merah totalling 1540 KK. A sample of these studies amounted to 30 KK the tecnique of data collection that is now, interview, observation, and documentation. Data analysis using Qualitative Descriptive. The result showed that the study data about shanges in Gondang Batak Toba tradition eraof modernization in te village of Tanah Merah Sub district Siak Hulu. Overall of the 30 respondents stated that many Yes. It is appropriate on the percentage of (61,67%) that aspects of the equipment in the tradition of Gondang Batak Toba have experienced changes in the era of modernization and the respondent who stated No (28,33%). The respondents starting Yes (19,2%) that the role of tradition Gondang Batak Toba native is still used in religious activities, ceremony of marriage, death, and for the party clan, and the respondents who stated No (80.8%). For the factors causes changes to the tradition of Gondang Batak Toba in the modernization of the respondents that answered Yes was (58,35%) and respondents who answered No was (41,65%). Thus it was concluded that a study about the change of the tradition of Gondang Batak Toba in the era of modernization in the village of Tanah Merah. Thus it was concluded that a study about the chenge of the tradition of Gondang Batak Toba in the era of modernization in the village of Tanah Merah Subdistricts Siak Hulu has undergone a change of modernization. This is in accordance with the benchmark. It is said to occur when the changers are at the range (51%-100%).Keywords: Change, Gondang Batak Toba, Tradition, Modernization.